Different Farmers Knowledge about Managing Soils Based on Educational Degree and Participation in Farmer Group Organization (A Descriptive Study on Sukatani and Wates Jaya Villages) - Destiyani, Rani Dwi; Adisyahputra, A; Sigit, Diana Vivanti (Biosfer: Jurnal Pendidikan Biologi, 2014)
Managing soils is a beneficial effort allowing plants to grow and have dense fruit as well as to avoid them from damaging. Lack of knowledge about soil management may be related to poor soil management performance. To identify differences on farmers knowledge about managing soils based on their educational degree and participation in farmer group organization, this research was conducted on Villages of Sukatani, Cianjur and Wates Jaya, Bogor from November to December 2012. A descriptive method with survey technique was used. Knowledge score using a multiple-choice test was obtained from 89 samples selected by simple random sampling. In prerequisite testing, data was found homogenous but in abnormal distribution. Therefore, the hypothesis testing then was carried out with non-parametric tests. The average comparative rate of farmers knowledge based on educational degree using the Kruskal-Wallis test showed a non significant differences (p > Î± at 0.393 > 0.05). This occurred because farmers gained the knowledge through parental manner. Similarly, the average comparative rate of farmers knowledge based on their participation in farmers organization using the Mann-Whitney U test also showed a non-significant differences (p > Î± at 0.770 > 0.05). This happened because the farmers did not receive information delivered by the organization appropriately or they did not use the organization as a source of information in managing the soils. As the conclusion, educational degree and participation in organization did not cause differences to farmers knowledge of soil management.